A REVIEW ON PHYTOCHEMICAL AND PHARMACOLOGICAL POTENTIAL OF WATERCRESS PLANT - Chaudhary, Sachin; Hisham, Hazar; Mohamed, Doha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Nasturtium officinale (family: Brassicaceae) that is commonly known as watercress is a fast-growing aquatic or semi-aquatic perennial plant native to Europe, Central Asia. It is a highly significant food supplement, extensively consumed with salad, juices, or other dishes as an ingredient, flavor, or garnish. The leaves are traditionally used as stomachic, depurative, diuretic, expectorant, hypoglycemic, odontalgic, and stimulant. Meanwhile, it has been used to treat jaundice, asthma, bronchitis, scurvy, tuberculosis, urinary tract infection, and calculi. N. officinale is rich in glucosinolates, carotenoids, polyphenols, as well as Vitamin C, Vitamin A, and Î±-tocopherol. It is the main source of iron, calcium, iodine, and folic acid.